2018
DOI: 10.1371/journal.pone.0193493
|View full text |Cite
|
Sign up to set email alerts
|

Out of the net: An agent-based model to study human movements influence on local-scale malaria transmission

Abstract: Though malaria control initiatives have markedly reduced malaria prevalence in recent decades, global eradication is far from actuality. Recent studies show that environmental and social heterogeneities in low-transmission settings have an increased weight in shaping malaria micro-epidemiology. New integrated and more localized control strategies should be developed and tested. Here we present a set of agent-based models designed to study the influence of local scale human movements on local scale malaria tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…ABM studies the dynamics of complex systems by simulating an array of heterogeneous individuals that make decisions, interact with each other, and learn from their experiences and the environment. The method is widely used to analyze epidemics [14][15][16][17]. Its advantage is in analyzing the factors that influence the spread of infectious diseases and the actions of individual actors [18].…”
Section: Introductionmentioning
confidence: 99%
“…ABM studies the dynamics of complex systems by simulating an array of heterogeneous individuals that make decisions, interact with each other, and learn from their experiences and the environment. The method is widely used to analyze epidemics [14][15][16][17]. Its advantage is in analyzing the factors that influence the spread of infectious diseases and the actions of individual actors [18].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we build on existing theoretical methods for the contribution of relapses to P. vivax transmission 24 29 , and develop a new, detailed individual-based simulation model of P. vivax transmission calibrated to data from many epidemiological studies from PNG and the Solomon Islands. Using this simulation model we investigate the impact of current and future malaria control interventions on P. vivax , and the potential impact of future treatment strategies with primaquine or tafenoquine.…”
Section: Introductionmentioning
confidence: 99%
“…The growing body of data arising from those 23 studies not only builds the evidence base required to accelerate the development process, 24 but it also provides an excellent foundation for developing models of host-seeking 25 behavior and experimentally validate the new tools at earlier stages. This paper 26 describes one such model: a fine-grained agent-based approach for modelling how indoor 27 insecticide treatments deployed as residues on bed nets affect the behavior and survival 28 of mosquitoes. 29 To capture the complex interactions between mosquitoes and a human host lying 30 beneath an insecticide-treated bed net, individual mosquito flight paths and local 31 interactions within the indoor environment are required.…”
mentioning
confidence: 99%
“…The influence of human movement on malaria transmission was studied with an 56 agent-based model in [27] who found that the spatial locations of malaria hotspots was 57 strongly influenced by human movement.…”
mentioning
confidence: 99%